The Effect of Economic Sector and Education on Income Inequality In IndonesiaThe Effect of Economic Sector and Education on Income Inequality In Indonesia - Irma Novianti; Fithriyah Fithriyah (Trunojoyo University of Madura, 2022)
This study aims to determine the impact of economic sector relations (agriculture, industrial, finance), education (literacy), provincial minimum wages and infrastructure (electricity, clean water and sanitation) on income inequality in Indonesia. The data used in this study are secondary data for 2010-2018 period from Central Bureau of Statistics and The Indonesia Database for Policy and Economic Research which is processed using panel data regression method and instrumental variables. Based on the estimation result, it shows that the variables of the agricultural sector, industrial sector, literacy and sanitation infrastructure are able to reduce income inequality in Indonesia in contrast to the result of the financial sector variables that have not been able to reduce income inequality. Meanwhile, the provincial minimum wage, electricity and clean water infrastructure variables have no effect on income inequality in Indonesia.